2023
DOI: 10.1002/cnma.202300319
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐induced Ordered Mesoporous Titania Molecular Sieves: A Unique and Highly Efficient Hetero‐phase Photocatalyst for Solar Hydrogen Generation

Sanjeev Gupta,
Surya Kumar Vatti,
Qinfen Gu
et al.

Abstract: The conversion of solar energy into fuel has gained significant interest, particularly in photocatalytic water splitting, and the materials that efficiently generate hydrogen from water or aqueous solution using solar irradiation are highly desired for the hydrogen economy. Photocatalysts made of N‐doped TiO2 are frequently utilized for breaking of water molecules in the process of generating hydrogen. To achieve this target, a unique defect‐induced nitrogen‐doped highly organized 2D‐hexagonal periodic mesopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…67 As expected, and in agreement with our EPR studies, we also observed an additional shoulder located at around 457.5 eV, attributed to Ti 3+ defects, while such a feature is almost absent or only a weak signal can be noticed in the case of P-25 which is as per the literature. 32,68 Furthermore, it can also be seen from Fig. 10 that the peaks of trivalent titanium in Yb-doped samples, viz.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…67 As expected, and in agreement with our EPR studies, we also observed an additional shoulder located at around 457.5 eV, attributed to Ti 3+ defects, while such a feature is almost absent or only a weak signal can be noticed in the case of P-25 which is as per the literature. 32,68 Furthermore, it can also be seen from Fig. 10 that the peaks of trivalent titanium in Yb-doped samples, viz.…”
Section: Resultsmentioning
confidence: 73%
“…, N-OMTs, are also included. 32 It may, however, be noticed from these figures that, unlike the singly doped N-OMT materials, the doubly doped OMTs, i.e. , Yb/N-TMF-127, calcined under standard conditions, viz.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations